The search for meaning at work: a critical analysis of the dominant and subordinate theoretical assumptions - Mercurio, Zachary A., author (Colorado State University. Libraries, 2016)
The search for meaning is a human activity that has transcended centuries of human civilization. As applied disciplines that investigate the development of organizations and the humans who comprise them, organization development (OD) and human resource development (HRD) scholars and practitioners have engaged in a steady stream of research and theorizing related to what "meaning" or "meaningfulness" in work is, how it develops, and most prominently in the literature, how it is operationalized. This paper seeks to add to the understanding of the concept of the meaningfulness of work through engaging in a critical analysis of the historical and theoretical assumptions of the meaningfulness of work and how these assumptions developed over time. In addition, through the interpretation of the reviewed theory, this paper will discuss the implications for future research on the meaning of work.
Meaning at work
Keywords: meaning of work; meaningfulness work; employee meaning